Effects of pinealectomy on the circadian release pattern of leptin in male rat - Baydas, G; Gursu, F; Canpolat, S; Konar, V; Yasar, A; Canatan, H; Kelestimur, H (Maghira & Maas Publications, 2001)
OBJECTIVES: Exogenous and endogenous melatonin decrease leptin release. It is not known whether melatonin also has an effect on circadian release pattern of leptin. So, this study was planned to investigate the possible changes in the circadian release of leptin following pinealectomy. METHODS: A group of rats were surgically pinealectomized while some others were exposed to sham operation. The animals were decapitated at 13.30 p.m. and 01.30 a.m. Serum leptin levels were measured by radioimmunoassay. RESULTS: Serum leptin levels at 13.30 p.m. were lower than the values at 01.30 a.m. in both pinealectomized (P<0.002) and sham rats P<0.001). Serum leptin levels measured at 13.30 p.m. and 01.30 a.m. were significantly elevated (P<0.05 and P<0.01, respectively) in the pinealectomized rats in comparison to sham animals. CONCLUSION: The circadian release of leptin does not seem to be regulated by melatonin release from the pineal gland whereas melatonin, physiologically released, may have a decreasing effect on leptin release.
Keywords: pinealectomy; leptin; circadian